A national survey of current practices of preparation and management of radical prostate radiotherapy patients during treatment. Issue 2 (May 2017) - Nightingale, H.; Conroy, R.; Elliott, T.; Coyle, C.; Wylie, J.P.; Choudhury, A.
Abstract: Aims: Radiotherapy is an important radical treatment for prostate cancer patients with services continually evolving. This survey aims to gain an insight in to the variation of radiotherapy practices in the UK, focussing on pre-treatment preparations, on-treatment review and management of radical prostate cancer patients undergoing radiotherapy. To our knowledge this is the first survey reported focussing on prostate radiotherapy practices with responses from a mix of health professionals. Materials and methods: A national survey was designed based on current known practices in supportive care and management of prostate cancer patients. The survey was distributed to lead radiotherapy personnel in radiotherapy services across the UK with a 77% response rate (n = 54). Results: Pre-treatment protocols were mandated in the majority of departments. Use of bladder filling (98%) and bowel emptying (66%) were frequently deployed. Bowel preparation varied between use of laxatives (13%) or enemas (41%) to achieve consistency. On-treatment reviews were carried out by a mix of health professionals; most commonly shared between oncologists and radiographers (20%). Radiographers reviewing patients were independent prescribers in 22% of departments. Toxicity grading tools were not used by almost half of departments (47%) either at baseline and/or on-treatment reviews. Written information about follow-up was given to patients towards the end of their radiotherapy; however, fewer departments included the length of hormone duration (13%). Conclusion: This survey has demonstrated variations in practice exist across the UK. These variations suggest that important questions about the best methods for treatment accuracy and patient management need to be established through further research. Highlights: Results of a national survey demonstrate wide variations in UK practice. Lack of a clear evidence base could be a contributing factor to such variation. Practices are developing in the advent of advance practice radiographers. Further research should be considered to establish best practice.